1999
DOI: 10.1562/0031-8655(1999)069<0091:dtrrdi>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Damage to Rat Retinal DNA Induced In Vivo by Visible Light

Abstract: Intense visible light can damage retinal photoreceptor cells by photochemical or thermal processes, leading to cell death. The precise mechanism of light-induced damage is unknown; however, oxidative stress is thought to be involved, based on the protective effect of antioxidants on the light-exposed retina. To explore the in vivo effects of light on retinal DNA, rats were exposed to intense visible light for up to 24 h and the time courses of single-strand breaks in restriction fragments containing the opsin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 14 publications
4
25
0
Order By: Relevance
“…27,48,49 This creates a stressful environment, with the metabolic byproducts that are formed, primarily reactive oxygen species, constantly attacking neuroretinal DNA. 27,50,51 Like the rest of the central nervous system, the retina depends on glia, mostly Muller cells and astrocytes, for proper function. We have discovered that the pathological appearance of astrocytes along the retinal blood vessel may result in microhemorrhage incidents.…”
Section: Discussionmentioning
confidence: 99%
“…27,48,49 This creates a stressful environment, with the metabolic byproducts that are formed, primarily reactive oxygen species, constantly attacking neuroretinal DNA. 27,50,51 Like the rest of the central nervous system, the retina depends on glia, mostly Muller cells and astrocytes, for proper function. We have discovered that the pathological appearance of astrocytes along the retinal blood vessel may result in microhemorrhage incidents.…”
Section: Discussionmentioning
confidence: 99%
“…The action spectrum of visible-light-induced retinal damage in rats suggests that the process involves rhodopsin bleaching (6). Reactive oxygen species (ROS) † appear to be involved in visible-light-induced retinal degeneration (7)(8)(9)(10) since antioxidants such as ascorbate (11,12), the superoxide dismutase mimic 2,2,6,6-tetramethyl-4-piperidinol-N-oxyl (TEMPOL) (13) and the hydroxyl radical scavenger dimenthylthiourea (DMTU) (7,14) prevent light-induced damage to rat photoreceptors. Evidence of antioxidant protection has come from morphological analysis of retinal cells (15,16) and by quantitation of the losses in rhodopsin (11,12) or visual-cell DNA (14,17,18) from rats exposed to intense light.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of antioxidant protection has come from morphological analysis of retinal cells (15,16) and by quantitation of the losses in rhodopsin (11,12) or visual-cell DNA (14,17,18) from rats exposed to intense light. Recently, methods to monitor DNA integrity have shown prevention of light-induced DNA strand breaks in rats treated with DMTU (9,13,19,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the retinal tissue is concerned, studies have demonstrated that it is particularly susceptible to oxidative damage. This is plausibly due its metabolic activity, since it contains a very high number of mitochondria and is subjected, by definition, to frequent if not continuous photo-chemical stress [15][16][17][18]. Therefore ocular nervous cells produce very high levels of radical species which, if not adequately neutralized, may cause severe damage to the hydrocarbon chains of unsaturated fatty acids, the aminoacid-residues, the nitrogen bases of nucleic acids, and carbohydrates [19].…”
mentioning
confidence: 99%